Modelling Customers’ Perception of the Quality of Services Provided by Builders: A Case of Victoria, Australia (Construction Economics and Building, 2021)
Consumer satisfaction is essential for quality assurance, business survival and economic prosperity. It can also be used as an indicator of the occurrence of defects in the houses delivered by builders. The objective of this study is to compare the quality of services provided by volume and small builders, and to develop a model for predicting the chance of occurrence of structural defects in houses. A list of home builders was obtained from Australia’s Housing Industry Association media release 2019. Thereafter, customer reviews of 10 volume builders and 107 small builders were obtained from publicly available data. Overall, 2336 reviews for volume-builders and 2037 reviews for small builders were analysed quantitatively. Further, using the scores provided by customers, the probability-based regression model for the structural integrity of residential buildings was developed. Generally, the research found that for volume-builders, customers have the highest satisfaction level for ‘customer service’ and the lowest satisfaction level for ‘plumbing and waterproofing’ work. However, for small builders, customers have the highest confidence in the ‘structural integrity’ of their buildings and the least confidence in projects ‘timeliness’. Clients can use the stochastic-based model to predict the probability that a builder could deliver a house with low structural defects. The model showed that if a customer service score for a particular builder is less than 3.3, then there is a higher chance of having structural defects. This research contributes to the body of knowledge by developing and validating the logistic regression model that can be used as a tool to assess the quality of services provided by home builders. Moreover, the research provides useful information which can assist builders to improve the quality of services they provide.